Wariantywność przekładu w ujęciu diachronicznym na podstawie wybranych tłumaczeń Mistrza i Małgorzaty Michaiła Bułhakowa na język polski - Sadowska, Monika (Acta Polono-Ruthenica, 2018)
The first edition of one of the most important and mysterious novels of the 20th century appeared more than fifty years ago. Despite the passage of time The Master and Margarita still enjoys popularity; it also intrigues and inspires. Until now five Polish translations of Bulgakov’s novel have appeared. It is known that the interpretation of the original might be expressed in the form of many potential texts that are communicatively equivalent. There is no doubt that it is the translator who plays a vital role in any translation; her/his personality, life experience, knowledge, skills, and also the times s/he lives in regulate the target text. That is why, no matter how many times a text is translated, the final product will always be different. Taking this into consideration, the author will compare the three Polish translations of Bulgakov’s Master and Margarita, paying attention to the diachronic perspective as far as linguistic norms are concerned, the modernity of language, and the way the anthroponyms are expressed.